Identifying shape and depth of unknown defects by using non-destructive testing - Tay, Rayson Teow Siang (2017)
Composites are gaining popularity over the years in both aerospace and marine industries. This is due to the high weight-to-strength ratio properties that composite materials have. However, it is also prone to mechanical damage, resulting to delamination and debonding of the layers internally. Hence, it is important in ensuring the health of the material. This report shows how Non-destructive testing (NDT) is able to observe internal structure of specimens while keeping the integrity of the whole structure intact. The advantages and limitations of different NDT methods will be discussed. Ultrasonic Tests and Shearography will be conducted on tidal blades manufactured from Energy Research Institute @ NTU (ERI@N). The blades are made up of a sandwiched honeycombed structure. It is observed that Ultrasonic Testing is quite an “impossible” feat due to the nature of both specimens and Ultrasonic Testing. However, this report try to push the limits of Ultrasonic Testing in attempt to evaluate the limitations of each methods. Ultrasonic A-scan is able to provide good depth measurements, but due to the attenuating nature of a sandwiched honeycombed structure, accurate results could not be obtained. Shearography, on the other hand, shows good positive results, but it could only analyse up to a certain depth. Difficulties and explanations will be highlighted in this report, hence evaluating the capabilities of each testing methods.